Hidden in plain sight, Chaetopterus dewysee sp. nov. (Chaetopteridae, Annelida) – A new species from Southern California - Tilic, Ekin; Rouse, Greg W. (European Journal of Taxonomy, 2020)
We describe a long-unnamed Chaetopterus Cuvier, 1830 species from southern California, using a combination of DNA barcoding and detailed morphological investigation employing high-resolution X-ray microtomography (micro-CT). Chaetopterus dewysee sp. nov. is not only one of the most dominant annelids in the benthic communities of the shallow end of the La Jolla submarine canyon, but also a well-established model for studying bioluminescence and has a published transcriptome. The description and naming of this southern Californian Chaetopterus is a step towards the much-needed revision of the group’s taxonomy and towards resolving the confusion over the ʻcosmopolitanʼ Chaetopterus variopedatus species complex. Micro-CT data showing details of both internal and external anatomy has been made freely available as the first annelid cybertype.